1997
DOI: 10.1086/515463
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Homozygous Point Mutations and a New Polymorphism in the COL17A1 Gene: Relation to Biological and Clinical Phenotypes of Junctional Epidermolysis Bullosa

Abstract: Junctional epidermolysis bullosa (JEB) is a clinically and biologically heterogeneous genodermatosis, characterized by trauma-induced blistering and healing without scarring but sometimes with skin atrophy. We investigated three unrelated patients with different JEB phenotypes. Patients 1 and 2 had generalized atrophic benign epidermolysis bullosa (GABEB), with features including skin atrophy and alopecia. Patient 3 had the localisata variant of JEB, with predominantly acral blistering and normal hair. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 29 publications
1
74
0
2
Order By: Relevance
“…3 and 4). Most are null mutations resulting in premature termination codons and, subsequently, in nonsense-mediated mRNA decay, whereas some missense mutations and small deletions have been reported (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…3 and 4). Most are null mutations resulting in premature termination codons and, subsequently, in nonsense-mediated mRNA decay, whereas some missense mutations and small deletions have been reported (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The role of collagen XVII in maintaining adhesion is supported by studies on pathological skin conditions. Mutations in the collagen XVII gene, COL17A1, lead to junctional epidermolysis bullosa, a hereditary blistering skin disease with epidermal detachment from the basement membrane (15)(16)(17)(18)(19)(20)(21). Tissue-bound and circulating IgG and IgA autoantibodies to collagen XVII are also associated with skin blistering in autoimmune bullous skin diseases (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Most COL17A1 mutations described to date are nonsense and deletion mutations leading to premature termination of translation and absence of type XVII collagen from the skin (Darling et al, 1997;Floeth et al, 1998;Gatalica et al, 1997;Jonkman et al, 1997;McGrath et al, 1995McGrath et al, , 1996aMcGrath et al, , 1996bScheffer et al, 1997;Schumann et al, 1997;Shimizu et al, 1998 887 acceptor splice-site mutations (Chavanas et al, 1997;Darling et al, 1998;Pulkkinen et al, 1999), one donor splice-site mutation (Pulkkinen et al, 1999), and four missense mutations (Floeth et al, 1998;McGrath et al, 1996a;Schumann et al, 1997;Tasanen et al, 2000) have been reported. In only one (Schumann et al, 1997) of the patients could type XVII collagen be immunologically detected in skin or cultured keratinocytes. The phenotype of JEB-nH caused by type XVII collagen deficiency may vary from generalized blistering with alopecia, also known as generalized atrophic benign epidermolysis bullosa (GABEB) (Hashimoto et al, 1976;Hintner and Wolff, 1982;Jonkman et al, 1996), to mild localized blistering without loss of hair (Floeth et al, 1998;Mazzanti et al, 1998;Schumann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In only one (Schumann et al, 1997) of the patients could type XVII collagen be immunologically detected in skin or cultured keratinocytes. The phenotype of JEB-nH caused by type XVII collagen deficiency may vary from generalized blistering with alopecia, also known as generalized atrophic benign epidermolysis bullosa (GABEB) (Hashimoto et al, 1976;Hintner and Wolff, 1982;Jonkman et al, 1996), to mild localized blistering without loss of hair (Floeth et al, 1998;Mazzanti et al, 1998;Schumann et al, 1997).In this study, we report for the first time homozygosity for a donor splice-site mutation in COL17A1 leading to multiple aberrant mRNA in a patient with generalized JEB-nH. The most abundant mRNA has an internal deletion of 390 bp, which leads to the expression of a shortened nonfunctional type XVII collagen polypeptide with a 130 amino acid deletion in the carboxy terminal half.…”
mentioning
confidence: 98%